EVALUATING THE REALITY OF MANUFACTURING STRATEGIES GUIDE / EXPLORATORY STUDY OF THE OPINIONS OF A SAMPLE OF ADMINISTRATIVE LEADERS WORKING IN THE SAMARRA PHARMACEUTICAL FACTORY - Ali Muhammad Huwayd Khater; Ahmed Badran Abdel Hussein (American Journals, 2024)
The research aims to evaluate the reality of applying pilot manufacturing strategies in the Samarra Pharmaceutical Factory, as the descriptive analytical approach was relied upon in studying the problem of the study. The two researchers measured the laboratory’s application of the six pilot manufacturing strategies, which are (comprehensive quality management, comprehensive productive maintenance, continuous improvement, and production in... Limited time, cellular manufacturing, rapid change) through a questionnaire form through which data was collected from the researched sample consisting of (60) individuals from various administrative levels. The questionnaire form was distributed to the members of the researched sample and was retrieved from (44) forms valid for statistical analysis. With a percentage of (73.3) In light of this, the study reached a set of conclusions, perhaps the most prominent of which is that the management of the Samarra Pharmaceuticals Factory has a vision of all guided manufacturing strategies, especially the comprehensive productive maintenance strategy, but it needs to show more attention to the comprehensive quality management strategy. In light of the research conclusions, the researchers presented a set of Perhaps the most prominent recommendations are for the laboratory management to maintain the application of the six guiding manufacturing strategies (total quality management, comprehensive productive maintenance, continuous improvement, on-time production, cellular manufacturing, rapid change) in its production processes to provide products and services that meet the needs of patients, especially at this time when The Iraqi environment witnesses a scarcity of laboratories that produce medical products. In addition, investing in this strategy is one of the means that increases the efficiency of production processes and reduces waste and loss of resources, because these strategies are compatible with each other and do not contradict each other when applied by administrative leaders.